A high-power DC-DC converter based dual active bridge for MVDC grids on offshore wind farms - Lee, Youngsil; Vakil, Gaurang; Feldman, Ralph; Watson, Alan James; Wheeler, Patrick (2016)
This paper presents the steady-state analysis of a high power step-up DC-DC converter based three-phase dual active bridge (3DAB) for use as a medium voltage (MV) DC-DC collector of offshore wind farms. An optimization procedure for a high-power medium frequency transformer is explained and moreover, a design of an optimal control phase shift angle is explained and verified through simulation. The comparisons with two scenarios are presented: 4MW converters for power conversion from low dc voltage (LVDC) of the wind turbine output terminal to 40kV MVDC grid of offshore wind farms. The proposed 3DAB DC-DC converter is investigated for the given scenarios in terms of losses of the semi-conductors and the magnetic part as well as the quantity of semi-conductors.